Analysis of vocational high school student metacognitive capabilities on geometry topics during the Covid-19 Pandemic - Ina Nurhayati; Nani Ratnaningsih; Khomsatun Nimah (Jurnal Pijar Mipa, 2022)
This study aims to analyze students' metacognitive abilities in terms of metacognitive awareness inventory on geometry topics during the Covid-19 pandemic. The method used in this research is a descriptive qualitative method. The research was conducted at Vocational High School Swadaya Karangnunggal Indonesia in the 2020/2021 academic year. The population in this study was the eleventh-grade student of office automation and governance, totaling 24 students. The questionnaire consists of 35 statement items with five indicators, namely planning (7 items), strategies for managing information (10 items), monitoring of understanding (7 items), improvement strategy (5 items), and evaluation (6 items). The stages in metacognitive ability are planning, monitoring, and evaluating stages. The results showed that students with good metacognitive abilities could carry out all metacognitive stages well, solving problems, planning, monitoring, and evaluating. Students with moderate metacognitive abilities cannot carry out all metacognitive stages in solving problems. They can carry out the planning stage, and some indicators cannot be completed properly. Then at the monitoring stage, they cannot monitor implementation activity to solve the problem because one of the subjects misunderstood the intent of the problem. The other subject experienced a calculation error when solving the problem. While at the evaluation stage, they could not complete all the indicators. Students with low metacognitive abilities cannot carry out all metacognitive stages in solving problems. They can only carry out the planning stage. Some indicators cannot be completed properly. Then they cannot carry out the monitoring and evaluation stages with all indicators.